Mental Health, Marital Breakdown, and Islamic Judicial Ethics: A Maqāṣid-Based Assessment of an Indonesian Religious Court Decision - Fadhly, Muhammad; Marwa, Marwa; Laseda, Nadila; Tahak, M. Hafiz Ridho Abdul; Abubakar, Fatum (IAIN Manado, 2025)
This study examines the Decision of the Ternate Religious Court Number 0062/Pdt.G/2017/PA. TTE regarding divorce lawsuits due to psychiatric disorders experienced by husbands, by placing the analysis from the perspective of maqāṣid al-syarī’ah . The research was conducted with a qualitative method through a normative juridical approach and maqāṣid al-syarī’ah analysis, and reinforced with field data from interviews to ensure the relevance between norms and practices. The findings of the study show that the judge granted the divorce lawsuit not solely because of the husband's psychiatric condition, but because it was proven that there were quarrels, disharmony, and domestic dysfunction that lasted continuously for more than six months. The judge's consideration was then analyzed based on the five principles of maqāṣid al-syarī’ah —hifdz al-din, hifdz al-aql, hifdz al-nafs, hifdz al-mal, and hifdz al-nasl—which, as a whole, affirmed that a divorce decision is the most beneficial option to maintain the safety, dignity, and rights of the wife.